Circulações artísticas no Cone Sul: notas preliminares sobre João Mottini e o mercado argentino de quadrinhos durante a Guerra Fria (décadas de 1940 a 1960) - Ivan Lima Gomes; Leonardo Pires Nascimento (Caravelle)
The period spanning the 1940s and 1960s decades is recognized for the establishment of an Argentinian comic book market in fairly complex terms. The country becomes a kind of pole of attraction for comic book artists from different countries, who blend their artistic trajectories to the demands of this market. We will develop this hypothesis based on an analysis of João Mottini’s career: his arrival in Argentina, his professional activities and subsequent return to Brazil.